Difficult airway management in an ankylosing spondylitis case using video laryngoscope: a case report - Limalvin, Nicholas Prathama; Kurniawan, Fajar (International Journal of Research in Medical Sciences, 2023)
Ankylosing spondylitis (AS) known as autoimmune disease with chronic inflammation within vertebral bone, characterized with bamboo spine. AS with cervical and temporomandibular joint involvement can lead to difficult airway. In this report, we present an AS patient with severe ARDS (acute respiratory distress syndrome) due to COVID-19 who was successfully intubated using video laryngoscope. A-37 years old male, came to emergency room in agitated condition, history of AS with cervical spine and temporomandibular joint involvement, history of pulmonary tuberculosis in 2008, and haven’t been vaccinated (COVID-19). This patient was diagnosed with severe ARDS due to COVID-19 with GCS 3-1-3, respiratory rate 36 times per minute, maximum peripheral saturation only 90% with Jackson Rees and pCO2 103 mmHg. These conditions are indication for endotracheal intubation. With the aid of video laryngoscope, endotracheal intubation was successfully performed. Improvements of peripheral saturation and blood gas analysis were obtained after intubation. This patient was included in the criteria for intubation due to respiratory rate over 30 times per minute and pCO2 more than 100 mmHg. Based on difficult airway predictor (MOANS, LEMON, RODS and SHORT), this patient was categorized as hard to ventilate and hard to intubate so it is necessary to prepare supraglottic airway device if intubation fails or surgical cricothyrotomy if intubation and supraglottic device fail. In difficult airway conditions, endotracheal intubation is ideally performed without muscle relaxants or awake intubation. The use of video laryngoscope is a recommended procedure in difficult airway management as in AS patient or in head and neck trauma cases. The availability of video laryngoscope in every hospital will maximize airway management in emergency room in Indonesia.